The effectiveness of static balloon atrioseptostomy for correcting hemodynamics in complex congenital heart diseases - O.O. Motrechko; A.V. Maksymenko; Yu.L. Kuzmenko; M.P. Radchenko; N.M. Rudenko (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate immediate and long-term results of static balloon atrioseptostomy in patients requiring enlargening of interatrial communication in complex congenital heart diseases. Materials and methods. During the period from February 2006 to January 2017 in Scientific and Practical Medical Center of Pediatric Cardiology and Cardiac Surgery (Kyiv, Ukraine) a group of 21 patients (12 boys and 9 girls) underwent static balloon atrioseptostomy. The age of patients ranged from 1.5 months to 10 years (mean age 12.2 ± 11.0 months), the average weight was 6.8 ± 2.5 kg (3–20.8 kg). In patients of group I (n = 12), which required increase in blood shunting at the atrial level, atrial septal defect diameter was 3.9 ± 1.3 mm (2–10 mm), average arterial blood saturation before procedure – 64.5 ± 2.8 % (7–83 %), transatrial gradient before procedure – 6.3 ± 2.1 mm Hg (3 to 12 mm Hg). In patients of group II (n = 9), which required atrioseptostomy for heart chambers decompression, average size of atrial septal defect was 3.3 ± 0.8 mm, average transatrial gradient – 13.2 ± 6.5 mm Hg. Results. The effective result was achieved in 17 (81 %) patients. Freedom from additional cardiac surgery after atrioseptostomy in 12 patients ranged from 6 to 60 months, average period 21 ± 15 months. Early mortality was 4.7 % (1 patient died). Late mortality 4.7 % (n = 1). Only one patient (4.7 %) had complications that needed conservative treatment. In group I average SatO2 level increased by 19.4 ± 14.6 %. Transatrial gradient decreased by 5.3 ± 1.7 mm Hg. In group II average SaO2 level increased by 5.1 ± 3.6 %. Transatrial gradient decreased by 8.5 ± 4.3 mm Hg. Conclusions. Static balloon atrioseptostomy is an efficient and safe minimally invasive method of enlarging interatrial communication.